Psychological impact of working in paediatric intensive care. A UK-wide prevalence study. Issue 5 (21st November 2019) - Jones, Gareth A L; Colville, Gillian A; Ramnarayan, Padmanabhan; Woolfall, Kerry; Heward, Yvonne; Morrison, Rachael; Savage, Amy; Fraser, James; Griksaitis, Michael J; Inwald, David P
Abstract : Objective: To determine the prevalence of work-related psychological distress in staff working in UK paediatric intensive care units (PICU). Design: Online (Qualtrics) staff questionnaire, conducted April to May 2018. Setting: Staff working in 29 PICUs and 10 PICU transport services were invited to participate. Participants: 1656 staff completed the survey: 1194 nurses, 270 physicians and 192 others. 234 (14%) respondents were male. Median age was 35 (IQR 28–44). Main outcome measures: The Moral Distress Scale-Revised (MDS-R) was used to look at moral distress, the abbreviated Maslach Burnout Inventory to examine the depersonalisation and emotional exhaustion domains of burnout, and the Trauma Screening Questionnaire (TSQ) to assess risk of post-traumatic stress disorder (PTSD). Results: 435/1194 (36%) nurses, 48/270 (18%) physicians and 19/192 (10%) other staff scored above the study threshold for moral distress (≥90 on MDS-R) (χ 2 test, p<0.00001). 594/1194 (50%) nurses, 99/270 (37%) physicians and 86/192 (45%) other staff had high burnout scores (χ 2 test, p=0.0004). 366/1194 (31%) nurses, 42/270 (16%) physicians and 21/192 (11%) other staff scored at risk for PTSD (χ 2 test, p<0.00001). Junior nurses were at highest risk of moral distress and PTSD, and junior doctors of burnout. Larger unit size was associated with higher MDS-R, burnout and TSQ scores. Conclusions: These results suggest that UK PICU staff are experiencing work-related distress. Further studies are needed to understand causation and to develop strategies for prevention and treatment.